The Role of the Parent in Psychotherapy with Children. Issue 2 (3rd April 2021) - Bruch, Hilde
Abstract : One of the outstanding differences of psychotherapy with children as distinguished from the treatment of adults is the fact that one's activity is not restricted to just one patient, the sick child, but that one has to deal with the parents and other significant people of the child's environment as well. Without undue exaggeration one might say that in many cases it is the parents who constitute the real problem in child psychiatry. They often seek help for their own difficulties in rearing their children, for their anxiety and guilt, and for their own annoyance and disappointment about the child's symptoms and shortcomings. I intend to discuss in this paper some problems in the handling of parents which I have encountered in the private practice of child psychiatry. I shall focus on those aspects which I personally have found difficult and many of which have remained unsolved problems in my daily work. I wish to apologize for presenting a paper which raises new questions instead of answering them. But I do hope to stimulate further thought by raising these questions and to clarify at least some of the issues involved.